KICHIK MAKTAB YOSHIDAGI O’QUVCHILARDA VATANPARVARLIK TUYG’USINI SHAKLLANTIRISHNING PEDAGOGIK ASOSLARI - Ismatov, A.I.; Isroilova, F. (SCIENCE and SOCIETY, 2020)
One of the main tasks facing primary education teachers today is how to create comfortable conditions for the development of patriotic feelings, self-education, the formation of willpower and self-confidence. The author also discuss the importance of patriotic education for younger students that is considered to be actual in the modern education system.